Digital Marketing Strategies In Attracting Generation Z Students At Private University - Yaser Arafat; Thomas Stefanus Kaihatu; David Sukardi Kodrat (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2025)
This study examines how digital marketing strategies influence Generation Z's enrollment intentions at Indonesian private universities through the Theory of Planned Behavior framework. Data collected from 212 Generation Z respondents across five major Indonesian cities were analyzed using PLS-SEM. Results reveal that Generation Z characteristics significantly influence enrollment intentions with digital marketing emerging as the strongest direct predictor. Contrary to conventional expectations, brand image demonstrated a negative relationship with enrollment intentions. Digital marketing positively moderates the relationship between Generation Z characteristics and enrollment intentions, while brand image exhibits a negative moderation effect. The model demonstrated substantial explanatory power, effectively capturing key determinants of enrollment decisions. These findings suggest a paradigm shift in higher education marketing for Generation Z, where authentic digital engagement outperforms traditional reputation-based approaches. High factor loadings for digital information sources, visual content, social media advertising, and direct digital interaction highlight specific aspects of digital marketing most valued by Generation Z. This research contributes both theoretical insights into digital-native decision-making and practical guidance for higher education institutions developing effective recruitment strategies in Indonesia's competitive educational landscape.